Kontekstualisasi Fikih Melalui Prinsip Kemaslahatan - Ansori, Ansori (Fakultas Syariah IAIN Purwokerto, 2008)
The existence of Islamic law (fiqh) wich is able to improve the society condition and to solve many problems is such a fact. Contextualize needs to be done continuously and one of the guidance is goodness principal.